1986
DOI: 10.1111/j.1476-5381.1986.tb11121.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of alfentanil and selected narcotic analgesics on the rate of action potential discharge of medullary respiratory neurones in anaesthetized rats

Abstract: 1 The effects of intravenous injections of alfentanil, fentanyl, phenoperidine or morphine on respiratory and peak inspiratory air flow rate, the diaphragm electromyogram (EMG), the activity recorded extracellularly from respiratory neurones located in the ventral respiratory group and the cardiovascular system were examined in anaesthetized rats. 2 Alfentanil produced dose-dependent changes in peripheral and central respiratory parameters, which were prevented by naloxone pretreatment. Minimal effects were pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Our results are in agreement with several previous reports where a decrease in RR was observed after fentanyl treatment. 14,45 In one of our recent studies, fentanyl and its analogs 2 , 5 , and 6 were also found to decrease respiratory frequency and cause respiratory depression following inhalation of smoke of these compounds in a static exposure assembly. 46 All μ-opioid receptor agonists, including fentanyl, produce dose-dependent respiratory depression.…”
Section: Discussionmentioning
confidence: 98%
“…Our results are in agreement with several previous reports where a decrease in RR was observed after fentanyl treatment. 14,45 In one of our recent studies, fentanyl and its analogs 2 , 5 , and 6 were also found to decrease respiratory frequency and cause respiratory depression following inhalation of smoke of these compounds in a static exposure assembly. 46 All μ-opioid receptor agonists, including fentanyl, produce dose-dependent respiratory depression.…”
Section: Discussionmentioning
confidence: 98%
“…These effects are accompanied by prolongation of discharges in inspiratory VRC neurons and prolongation of diaphragmatic EMG activity. The prolongation of inspiration is linked to effects on respiratory phase‐terminating neurons (Fone & Wilson, ), which are widely distributed in the bulbar respiratory network (Ezure, ).…”
Section: Medullary Neurons Distributed Throughout the Bulbar Respiratmentioning
confidence: 99%
“…Lowering of firing threshold, enhancement of spike train oscillations and bursts and prolongation of discharges by lowest effective doses of fentanyl could represent compensatory adjustments in the brain stem respiratory network to override opioid blunting of CO2/pH chemosensitivity. respiratory neuron discharges; burst and oscillation patterns; opioid actions, bursts and oscillations; opioid lowers respiratory neuron discharge threshold NEURONS in the dorsolateral pons and ventral respiratory column (VRC) of the medulla exhibit a three-phase rhythm and modulate tidal volume in human and nonhuman mammals (38,39,44), and several studies have demonstrated how opiates affect VRC and pontine respiratory neuron rhythm and excitability (11,16,18,20,26,29,31,32,36,48,51). Low doses of opiates withor ␦-receptor affinity slow respiratory frequency, with lesser effects on depth of respiration in humans (9,10,14,47) and cats (26,28).…”
mentioning
confidence: 99%